2018
DOI: 10.1038/s41467-018-04723-6
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering hidden brain state dynamics that regulate performance and decision-making during cognition

Abstract: Human cognition is influenced not only by external task demands but also latent mental processes and brain states that change over time. Here, we use novel Bayesian switching dynamical systems algorithm to identify hidden brain states and determine that these states are only weakly aligned with external task conditions. We compute state transition probabilities and demonstrate how dynamic transitions between hidden states allow flexible reconfiguration of functional brain circuits. Crucially, we identify laten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
186
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(203 citation statements)
references
References 70 publications
8
186
1
Order By: Relevance
“…It has been proposed that such three networks are the "core" neurocognitive networks and their functional interactions are important for complex, high-order cognitive functions (Menon, 2011) and could be responsible for psychiatric and neurological disorders, such as depression (Berman et al, 2011), schizophrenia (Palaniyappan et al, 2011), and dementia (Zhou et al, 2010;Yu et al, 2017). Recently, researchers have found that the dynamic network switch supports flexible attention (mainly via DAN and VAN) and cognitive control (mainly via FPN) to meet time-varying changes in cognitive demands, and the loss of such optimized dynamics may lead to poor task performance in a decision-making task (Taghia et al, 2018). Such a flexibility among the three networks could be associated with Attention-deficit/hyperactivity disorder (ADHD) and schizophrenia (Supekar et al, 2019).…”
Section: Increased Inter-network Fc Flexibilitymentioning
confidence: 99%
“…It has been proposed that such three networks are the "core" neurocognitive networks and their functional interactions are important for complex, high-order cognitive functions (Menon, 2011) and could be responsible for psychiatric and neurological disorders, such as depression (Berman et al, 2011), schizophrenia (Palaniyappan et al, 2011), and dementia (Zhou et al, 2010;Yu et al, 2017). Recently, researchers have found that the dynamic network switch supports flexible attention (mainly via DAN and VAN) and cognitive control (mainly via FPN) to meet time-varying changes in cognitive demands, and the loss of such optimized dynamics may lead to poor task performance in a decision-making task (Taghia et al, 2018). Such a flexibility among the three networks could be associated with Attention-deficit/hyperactivity disorder (ADHD) and schizophrenia (Supekar et al, 2019).…”
Section: Increased Inter-network Fc Flexibilitymentioning
confidence: 99%
“…The HMM has recently been applied to model neural dynamics inferred from magnetoencephalography (MEG) (Baker et al, 2014;Quinn et al, 2018;Vidaurre et al, 2016) as well as task-based and resting-state functional MRI data (Ryali et al, 2016;Vidaurre et al, 2017a;Vidaurre et al, 2017b;Taghia et al, 2018). These seminal studies provide evidence for the utility of the HMM in characterizing dynamic interactions between brain networks in healthy individuals and show that the frequency of state transitions increases with age (Ryali et al, 2016) and transitions can be organized hierarchically into cognitive and sensorimotor metastates, with dwell times in these putative metastases being heritable and correlating with cognitive traits (Vidaurre et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…A principled framework to tackle this issue is to model neural population dynamics using hidden Markov models (HMMs) [10]. These state space models can identify hidden states from population activity patterns in single trials, and have been successfully deployed in a variety of tasks and species from C. Elegans [5] to rodents [11][12][13][14], primates [15][16][17][18] and humans [19,20]. Hidden Markov models segment single-trial population activity into sequences in an unsupervised manner by inferring hidden states from multi-neuron firing patterns.…”
Section: Introductionmentioning
confidence: 99%